การพัฒนาแนวทางการดำเนินงานกาประกันคุณภาพภายในของสถานศึกษา สังกัดสำนักงานเขตพ้ืนที่การศึกษาประถมศึกษาร้อยเอ็ด เขต 3 - โคตรสมบัติ สวัสดิ์ (Journal of Graduate School Sakon Nakhon Rajabhat University, 2017)
Abstract The purposes of this research is to study the current situation 1) The desirable state of internal quality assurance of the school 2) Study on the development and internal quality assurance of the school under the office of Roi Et Primary Educational Service Area 3 The samples were 344 of 172 administrators and 172 teachers in the academic year 2015 Data were collected using was a questionnaire and interview Statistical analysis for frequency, percentage mean ,standard deviation, and Content Analysis by descriptive lecture; The research results are as follows; Internal quality assurance of the school under the office of Roi Et Primary Educational Service Area 3 overall is operating at the highest level in every aspect. The desirable state internal quality assurance of the school under the office of Roi Et Primary Educational Service Area 3 overall The characteristics at the highest level in every aspect. 3. The needs of the development of internal quality assurance auditing Under the office of Roi Et Primary Educational Service Area 3 region showed that the high needs most is to set the standard of educational institutions. The second is the study of school management plan aimed at quality standard study of tourism study. Management and information. The implementation of development plan of school education management And provide the internal quality assessment standards of educational institutions, respectively. The results mentioned operation development of internal quality assurance system of schools with good performance. The school will have to rely on the concept of development of systems of Deming (Plan Do Check Act) is the basis of practice. Every step of the operation and development of internal quality assurance system for schools. To focus on school based management (School-Based Management: SMB) with the relevant parties, consisting of the school board. Parents, community and schools to participate. Joint action and joint decision activities. To increase the efficiency and effectiveness of management education. And use the principle of cooperation from all sectors to obtain support and promote the quality education together. 4. developing Guidelines to operate internal quality assurance of the school under the office of Roi Et Primary Educational Service Area 3 administrators and teachers should be exploring the needs of students, sharing a strategic plan Operational plans systematically. Supervision and monitoring evolution projects/activities to parents, community, government organization and private sector participation in the provision of and developing knowledge and understanding about the education quality All stakeholders of the school must be working to benefit to the student The awareness and perceived value of function systematically The orientation and project/activity by using the self assessment, the quality evaluation of external organizations or were created to solve a problem or school students development As well as other findings related to the base to determine the operation to achieve the efficiency.